SDN and Traffic Fine Operation - Subin Wang; Yongqing Zhu (Dianxin kexue)
On the basis of analyzing the real use cases of network traffic optimization, an idea and system architecture were presented, which abstracted the current network to the overlay network and used the SDN controller to control the overlay network for smart traffic steering and optimization according the policies defined by users. This solution can be widely applied in multiple different type of IP networks, and utilize the mature protocols to migrate the existed network to SDN smoothly with the benefits from SDN.